2005
DOI: 10.2196/jmir.7.3.e36
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Internet Search Activity on a Major Search Engine, United States 2001-2003

Abstract: Background To locate online health information, Internet users typically use a search engine, such as Yahoo! or Google. We studied Yahoo! search activity related to the 23 most common cancers in the United States.Objective The objective was to test three potential correlates of Yahoo! cancer search activity—estimated cancer incidence, estimated cancer mortality, and the volume of cancer news coverage—and to study the periodicity of and peaks in Yahoo! cancer search activity.Methods Yahoo! cancer search activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 23 publications
2
96
0
1
Order By: Relevance
“…The same year Cooper, Mallon, Leadbetter, Pollack & Peipins [10] described the use of Internet search volume for cancer-related topics. Since then there have been several papers that have examined web search data in numerous fields.…”
Section: Using Google Searches Totals To Predict Social Trendsmentioning
confidence: 99%
“…The same year Cooper, Mallon, Leadbetter, Pollack & Peipins [10] described the use of Internet search volume for cancer-related topics. Since then there have been several papers that have examined web search data in numerous fields.…”
Section: Using Google Searches Totals To Predict Social Trendsmentioning
confidence: 99%
“…When appropriately trained, these methods can be quite accurate; for example, many of the cited models can produce near real-time estimates of case counts with correlations upwards of r = 0.95. The collection of disease surveillance work cited above has estimated incidence for a wide variety of infectious and noninfectious conditions: avian influenza [52], cancer [55], chicken pox [67], cholera [81], dengue [50,53,84], dysentery [76], gastroenteritis [56,61,67], gonorrhea [64], hand foot and mouth disease (HFMD) [72], HIV/AIDS [75,76], influenza [34,36,54,57,59,62,63,65,67,68,71,74,[77][78][79][80]82,83,[85][86][87][88][89][90][91][92][93], kidney stones [51], listeriosis [70], malaria [66], methicillin-resistant Staphylococcus aureus (MRSA) [58]<...>…”
Section: Author Summarymentioning
confidence: 99%
“…Openness. Deep access to search queries from Baidu, a Chinese-language search engine serving mostly the Chinese market (http://www.baidu.com) [64,74,76]; Google [36,[50][51][52][53][54][56][57][58][59][60][65][66][67][69][70][71][72][73]75]; Yahoo [55,68]; and Yandex, a search engine serving mostly Russia and Slavic countries in Russian (http://www.yandex.ru), English (http://www. yandex.com), and Turkish (http://www.yandex.com.tr) [75], as well as purpose-built health website search queries [61][62][63] and access logs [72,93] are available only to those within the organizations, upon payment of an often-substantial fee, or by some other special arrangement.…”
Section: Author Summarymentioning
confidence: 99%
“…As explained in Choi and Varian (2012), the pioneer studies that advocate the usefulness of web search data in forecasting macroeconomic statistics (Ettredge, Gerdes, & Karuga, 2005) and presenting Internet search activity as an innovative tool for passive surveillance of health information-seeking behavior (Cooper, Mallon, Leadbetter, Pollack, & Peipins, 2005) were followed by studies in epidemiology (Polgreen, Chen, Pennock, Nelson, & Weinstein, 2008;Ginsberg et al, 2009) that showed that search data could predict the incidence of influenza-like diseases. Da, Engelberg, and Gao (2011) propose the Google Trends search volume index as direct measure for investor attention while Vosen and Schmidt (2011) establish that Google Trends is a very promising new source of data to forecast private consumption, since in almost all experiments conducted the Google Indicators' in-sample and out-of-sample predictive power proved to be better than that of the conventional survey-based indicators.…”
Section: Online and Traditional Sentiment Analysismentioning
confidence: 99%